The Effect Learning Method on Students’ Speaking Skill and Critical Thinking at STKIP Kusuma Negara Jakarta - Megawati Megawati (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
This research aims to identify the effect of learning method on students’ speaking skill, the effect learning method on critical thinking, and the effect learning method learning method on students’ speaking skill and critical thinking. Lecturer was chosen Students Team Achievement Division (STAD) and Jigsaw. Through learning method, researcher supposed to the students to get fluency in speaking English This research uses experimental research. Sample of this research was 30 students sixth semester Educational English Program at STKIP Kusumanegara. It was divided into two classes, that is, experiment class and control class. Collecting of the data was by using questionnaire and test speaking. Data was analysed using Kolmogorov Smirnow, to identify the data was normality. Then data was analysed by using Levenue to define that the data was homogeinity. It was obtained hypothesis, from the table Multivariate Test with F=74.642, sig 0.000 (<0.05). The results show that there is significant effect learning method towards Speaking Skills and Critical Thinking. It represents that F=145.499, p-value for category speaking skill (Y1) is 0.000 (<0.05), in which H0 is rejected or there is differences significant between students’ speaking skill in students’ group which was given by learning method with STAD with students’ speaking skill in students’ group which was given by learning method with Jigsaw. It represents that F=145.499, p-value for category critical thinking (Y2) is 0.000 (<0.05), in which H0 is rejected or there is differences significant between critical thinking in students’ group which was given by learning method with STAD with critical thinking in students’ group which was given by learning method with Jigsaw.